Food and macronutrient intake of elite Ethiopian distance runners - Beis, L. Y.; Willkomm, L.; Ross, R.; Bekele, Z.; Wolde, B.; Fudge, B.; Pitsiladis, Y. P. (Journal of the International Society of Sports Nutrition, 2011)
Explanations for the phenomenal success of East African distance runners include unique dietary practices. The aim of the present study was to assess the food and macronutrient intake of elite Ethiopian distance runners during a period of high intensity exercise training at altitude and prior to major competition. Methods: The dietary intake of 10 highly-trained Ethiopian long distance runners, living and training at high altitude (approximately 2400 m above sea level) was assessed during a 7 day period of intense training prior to competition using the standard weighed intake method. Training was also assessed using an activity/training diary. Results: Body mass was stable (i.e., was well maintained) over the assessment period (pre: 56.7 +/- 4.3 kg vs. post: 56.6 +/- 4.2 kg, P = 0.54; mean +/- SD). The diet comprised of 13375 +/- 1378 kJ and was high in carbohydrate (64.3 +/- 2.6 %, 545 +/- 49 g, 9.7 +/- 0.9 g/kg). Fat and protein intake was 23.3 +/- 2.1 % (83 +/- 14 g) and 12.4 +/- 0.6 % (99 +/- 13 g, 1.8 +/- 0.2 g/kg), respectively. Fluid intake comprised mainly of water (1751 +/- 583 mL), while no fluids were consumed before or during training with only modest amounts being consumed following training. Conclusions: Similar to previous studies in elite Kenyan distance runners, the diet of these elite Ethiopian distance runners met most recommendations of endurance athletes for macronutrient intake but not for fluid intake.